Fall Panicum: Biology and Control in Sugarcane - Dennis C. Odero; Brent Sellers (EDIS)
This publication describes the biology and control options for fall panicum in sugarcane to assist growers, county Extension faculty, and crop consultants in making correct identification and effective management decisions to help mitigate its impact on sugarcane. Written by D. Calvin Odero and Brent Sellers, and published by the UF/IFAS Agronomy Department, revised February 2022.